KUALITAS LAPORAN KEUANGAN DAN KONSERVATISME AKUNTANSI PASCA IFRS - Eni Indriani; Robith Hudaya; Widia Astuti (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2021)
Conservatism emerged as a result of the accrual approach in preparing financial statements. Accounting conservatism encourages caution so that companies in their financial reporting do not rush to recognize profits, but recognize losses as soon as possible. This research was conducted with the aim of knowing the effect of accounting conservatism on the quality of financial statements after the convergence of IFRS (International Financial Reporting Standards) in Indonesia at manufacturing companies that experienced investment growth in 2015-2019. In order to achieve the objectives of this study, the empirical model uses a simple linear regression equation, with a feasibility test of the model through the coefficient of determination (R 2) and statistical t-test. The results of statistical data processing show that the Accounting Conservatism (AC) variable has a t-count value of 6.737 with a variable significance level of 0.000, this means that Accounting Conservatism (AC) has a significant effect on the quality of financial statements (DACC). The positive direction of the variable coefficient value shows that the independent variable has a positive effect on the dependent variable. This means that the application of convergent Financial Accounting Standards to IFRS in Indonesia provides good news for stakeholders, because it can improve the quality of financial reports and reduce motivation for earnings management practices that can mislead users of financial statements in making economic decisions. Keywords: Accounting conservatism, quality of financial reports, accounting standards, economic decisions